Parameters of Anodic Alumina Determined from Fabry – Perot Oscillations in Specular Reflection Spectra - I. V. Gasenkova; N. I. Mukhurov; I. M. Andrukhovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The Fabry – Perot oscillations in specular reflection spectra in the visible wavelength range depending on the anodic alumina thickness have been investigated. The anodic alumina was formed in 1.0 M H2SO4 aqueous solution with the 1:1 water to ethylene glycol solution additive. The oxides fabrication conditions have been established whose reflection spectra were characterized by high intensity of oscillations to be used in sensor structures. Using these optical oscillations data, the anodic alumina effective refractive indices have been calculated; the increase by 0.04 has been revealed in the isopropyl alcohol solution compared to the air medium for the 2 to 5 micrometer thick samples. The ability to determine the anodic alumina porosity using the Fabry – Perot oscillation shift in the different refractive indices media has been shown. A good agreement between the porosity values obtained from the reflection spectra calculations and the electron microscopic images has been established.